Bond response of NSM CFRP strips in concrete under sustained loading and different temperature and humidity conditions. (15th May 2018) - Emara, M.; Torres, L.; Baena, M.; Barris, C.; Cahís, X.
Abstract: Near Surface Mounted (NSM) reinforcement has been increasingly recognized as an efficient technique for strengthening Reinforced Concrete (RC) structures using Fiber Reinforced Polymer (FRP) reinforcement. Although a number of studies have investigated the short-term bond behavior between NSM FRP and concrete, little work has been done on its long-term behavior under sustained loading. This paper aims to experimentally investigate the bond response of NSM Carbon FRP (CFRP) strips in concrete under sustained loading and different temperature and humidity conditions. Thirty-three single shear pull-out specimens were subjected to monotonic and sustained loading. The long-term pull-out specimens were subjected to different environmental regimes including four combinations of temperature, humidity and sustained loading. For each environmental combination, three bonded lengths were tested and two levels of sustained loading were applied. Specimens were kept loaded and conditioned in a climatic chamber for 1000 h, while the slip evolution with time was monitored throughout the testing period. Results revealed that the changes in the parameters being studied did have a relevant effect on the bond response.